Low band gap donor-acceptor-donor compounds containing carbazole and naphthalene diimide units: Synthesis, electropolymerization and spectroelectrochemical behaviour. (20th October 2020) - Rybakiewicz, Renata; Ganczarczyk, Roman; Charyton, Martyna; Skorka, Lukasz; Ledwon, Przemyslaw; Nowakowski, Robert; Zagorska, Malgorzata; Pron, Adam
Abstract: A new DπAπD compound consisting of naphthalene diimide core-functionalized with 1, 4-phenylene-functionalized carbazole, namely 2, 6-bis[4-(9 H -carbazol-9-yl)phenyl]- N, N' -bis(2-ethylhexyl)-1, 4, 5, 8-naphthalenetetracarboxylic acid diimide (CNDI ) was synthesized. Its redox properties (reduction and oxidation potentials, electron affinities (EA) and ionization potentials (IP)) were compared with those of 4, 7-bis(4-(9 H -carbazol-9-yl)phenyl)benzo[ c ][1, 2, 5]thiadiazole (CBTD ) – a specially synthesized reference compound containing identical Dπ- units and significantly weaker acceptor (benzothiadiazole). It was demonstrated that the acceptor strength, determined as the index of the spatial extent of the charge transfer, D C T P, only weakly influenced the molecule oxidation potential and by consequence its ionization potential. To the contrary, strong effect of charge transfer, expressed by D C T P, was found for the reduction potential of CNDI and CBTD, showing significantly higher reduction potential of the former leading to much higher |EA|. CNDI could be electrochemically polymerized yielding a low band gap polymer (Eg  = 1.63 eV) of ambipolar character, exhibiting low ionization potential (IP = 5.48 eV) and high electron affinity (|EA| = 3.85 eV). In its cyclic voltammograms polyCNDI shows five redox states, namely neutral, first and second reduction and first and second oxidation ones. As revealed by detailed studies of electrochromic parameters only three redox states (neutral, first reduction and first oxidation) demonstrate good electrochromic performance.